Evaluation of an e-Learning teaching innovation to assist clinical radiation therapy educators in the provision of student feedback - O'Neill, Mary; Kearney, Maeve; Leech, Michelle; Davis, Siobhan (My University, 2021)
Background: Clinical placement is an integral part of the Radiation Therapy undergraduate programme. Feedback and formative assessment during clinical placement are regarded as key to developing clinical skills and competencies. Students regularly report dissatisfaction with the feedback process while clinical educators report heavy clinical workloads and a lack of guidance on feedback mechanisms as barriers to providing meaningful student feedback. Methods: An eLearning teaching intervention was developed to support radiation therapists in the provision of student feedback in the clinic. Thematic analysis was used to report attitudes to feedback and feedback practices collected in a pre and a post intervention evaluation. Results: 30 radiation therapists completed the module and pre and post intervention evaluations. Prior to taking the module just over half of respondents stated that they offered regular and on-going feedback throughout the student's placement. Positive attitudes to feedback were reported. Following completion of the eLearning tool respondents reported a higher level of confidence in the provision of student feedback and almost 70% said the module had changed how they would approach the feedback process by using feedback models in the future. Discussion: Good and timely feedback is essential and allows a student opportunity to improve prior to the end of the placement. It also teaches students how to self-assess and self-reflect - skills that they can use in continuous professional development after they graduate. Radiation therapists appreciate the structure that using a model in the feedback process offers. Conclusion: This eLearning teaching intervention was received favourably by radiation therapists who are key to creating a culture of feedback in the clinical environment that will facilitate students in becoming competent healthcare professionals.
PUBLISHED
Keywords: Clinical placement; Education; Feedback; Radiation therapy; Cancer; Inclusive Society; Clinical Supervision; EDUCATION